Effects of wood kraft pulp as a partial replacement for roughage on rumen fermentation and productivity in dairy cows. (26th April 2022) - Yamamoto, Hiroshi; Shimizu, Yasuhiro; Hasunuma, Toshiya; Manabe, Noriyoshi; Osawa, Ryo; Kawashima, Kenji; Fukui, Yoji; Ueno, Yutaka; Kurosu, Kazuhiro; Mizuguchi, Hitoshi; Terada, Fuminori; Sato, Shigeru; et al.
Abstract: In this study, we evaluated the partial replacement of roughage with wood kraft pulp (KP) on rumen fermentation and productivity of dairy cows. Eighteen cows were divided into control and KP groups. The KP group started adaptation to KP 3 weeks before calving; after calving, they were fed a total mixed ration for 12 weeks, wherein 18% Timothy hay was replaced with KP. The dry matter intake, body weight, and milk yield and composition were similar in the control and KP groups. The average daily rumen pH was higher with KP feeding, and the average daily ruminal temperature remained lower at 16 days after calving ( P < 0.05). The concentration of volatile fatty acids remained unaltered, the molar proportion of acetic acid decreased, and the molar proportion of propionic acid increased, indicating a low acetic acid:propionic acid ratio ( P < 0.05). Lipopolysaccharide activity in the rumen fluid was higher in the KP group ( P < 0.05); however, the rumen microbiota were unaffected. The digestibility of dry matter and neutral detergent fiber increased 12 weeks after calving, whereas excretion of urinary nitrogen decreased ( P < 0.05). Partial replacement of roughage with KP did not suppress rumen fermentation and maintained postpartum productivity.